The analytics revolution : how to improve your business by making analytics operational in the big data era - Franks, Bill, 1968- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"Lead your organization into the industrial revolution of analytics with The Analytics RevolutionThe topics of big data and analytics continue to be among the most discussed and pursued in the business world today. While a decade ago many people still questioned whether or not data and analytics would help improve their businesses, today virtually no one questions the value that analytics brings to the table. The Analytics Revolution focuses on how this evolution has come to pass and explores the next wave of evolution that is underway. Making analytics operational involves automating and embedding analytics directly into business processes and allowing the analytics to prescribe and make decisions. It is already occurring all around us whether we know it or not. The Analytics Revolution delves into the requirements for laying a solid technical and organizational foundation that is capable of supporting operational analytics at scale, and covers factors to consider if an organization is to succeed in making analytics operational. Along the way, you'll learn how changes in technology and the business environment have led to the necessity of both incorporating big data into analytic processes and making them operational. The book cuts straight through the considerable marketplace hype and focuses on what is really important. The book includes: An overview of what operational analytics are and what trends lead us to them Tips on structuring technology infrastructure and analytics organizations to succeed A discussion of how to change corporate culture to enable both faster discovery of important new analytics and quicker implementation cycles of what is discovered Guidance on how to justify, implement, and govern operational analytics The Analytics Revolution gives you everything you need to implement operational analytic processes with big data"--
Preface -- Acknowledgments -- Part one. The revolution has begun. Chapter 1. Understanding operational analytics ; Defining operational analytics ; Welcome to analytics 3.0 ; How analytics are changing business ; Putting operational analytics in perspective ; Wrap up ; Notes ; Chapter 2. More data ; "More data" Big data! ; Cutting through the hype ; Preparing for big data ; Putting big data in context ; Wrap up ; Notes ; Chapter 3. Operational analytics in action ; Improving customer experiences ; Time is of the essence ; Making us safer ; Increasing operational efficiency ; Improving our lives in the future ; Finding unexpected value in data ; Wrap up ; Notes -- Part two. Laying the foundation. Chapter 4. Want budget? Build the business case! ; Setting the priorities ; Choosing the right decision criteria ; A business case framework to consider tips for creating a winning business case ; Wrap up ; Notes ; Chapter 5. Creating an analytic platform ; Planning building using ; Wrap up ; Notes ; Chapter 6. Governance and privacy ; Setting the stage for governance ; Deciding where analytics happen ; Governing operational analytics privacy ; Wrap up ; Notes -- Part three. Making analytics operational. Chapter 7. The analytics ; Creating operational analytic processes ; Expanding into new analytic disciplines ; Focusing analytic efforts ; Comparing analytic approaches ; Lessons from the past ; Wrap up ; Notes ; Chapter 8. The analytics organization ; A major shift has occurred ; Staffing organizing ; Succeeding ; Wrap up ; Notes ; Chapter 9. The analytics culture ; Instilling the proper mindset ; Implementing effective policies ; Facilitating success ; Enabling and handling the right failures ; Wrap up ; Notes -- Conclusion. Join the revolution! -- Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Business intelligence; Big data; BUSINESS & ECONOMICS -- General; Big data; Business intelligence; Electronic books; Electronic books